REKONTEKSTUALISASI ADAB KEPADA GURU DALAM ORGANISASI DAKWAH KEMANUSIAAN INDONESIA PERSPEKTIF TAZKIRAT AL-SĀMIʿ WA AL-MUTAKALLIM - Maskuri Latif (PT. Sulthan Journal Publisher, 2026)
This study examines the concept of taʿẓīm al-ʿālim (reverence for scholars) within the Islamic intellectual tradition and its relevance to ethical leadership and governance in humanitarian dakwah organizations in Indonesia. In recent years, particularly since 2021, Islamic philanthropic and dakwah institutions have expanded significantly, creating tensions between charismatic leadership based on ulama authority and the demand for participatory, transparent, and accountable organizational governance. Despite the growing literature on religious authority and charismatic leadership, limited studies connect these discussions with the concept of taʿẓīm al-ʿālim and its implications for organizational ethics in Islamic institutions. This research employs a Systematic Literature Review (SLR) combined with bibliometric analysis using VOSviewer on Scopus-indexed publications concerning “charismatic religious leadership” and “religious authority in Islam”. In addition, a critical textual analysis of Tazkirat al-Sāmiʿ wa al-Mutakallim by Ibn Jamāʿah is conducted. Eight selected articles are thematically analyzed to map relationships between authority, power, and religious leadership, and then compared with the classical ethical framework of reverence toward scholars. The findings show that taʿẓīm al-ʿālim aligns with contemporary understandings of religious authority rooted in knowledge, moral integrity, and community legitimacy, while emphasizing ethical responsibility and adab. Values such as trustworthiness (amanah), exemplary conduct, service, and respect for knowledge can be translated into organizational ethics through codes of conduct, consultative mechanisms, and institutional standards, contributing to a more accountable and civilized model of dakwah governance.